The LifeWebs project: A call for data describing plant-herbivore interaction networks - Fayle, Tom Maurice (2016)
Understanding global drivers of changes in species interacons is vital, both in terms of improving our knowledge of fundamental large-scale ecology, and in order to predict and protect against human-driven changes to ecosystems. Here we present the LifeWebs project, which aims to collate existing data on interacon networks in order to understand their large-scale paerns. Inially we will collate data relating to plant?herbivore interacons, and this arcle is a call for contributions. We outline the kinds of data in which we are interested, the procedure for making contribuons, and what contributors can expect in terms of co-authorship on subsequent papers and access to the database for conducting their own analyses.